Fetal oxygenation in the last weeks of pregnancy evaluated through the umbilical cord blood gas analysis - Filippi, Luca; Scaramuzzo, Rosa Teresa; Pascarella, Francesca; Pini, Alessandro; Morganti, Riccardo; Cammalleri, Maurizio; Bagnoli, Paola; Ciantelli, Massimiliano (Frontiers in Pediatrics, 2023)
Introduction. Embryo and fetus grow and mature over the first trimester of pregnancy in a dynamic hypoxic environment, where placenta development assures an increased oxygen availability. However, it is unclear whether and how oxygenation changes in the later trimesters and, more specifically, in the last weeks of pregnancy. Methods. Observational study that evaluated the gas analysis of the umbilical cord blood collected from a cohort of healthy newborns with gestational age ≥ 37 weeks. Umbilical venous and arterial oxygen levels as well as fetal oxygen extraction were calculated to establish whether oxygenation level changes over the last weeks of pregnancy. In addition, fetal lactate, and carbon dioxide production were analyzed to establish whether oxygen oscillations may induce metabolic effects in utero. Results. This study demonstrates a progressive increase in fetal oxygenation levels from the 37th to the 41st weeks of gestation (mean venous PaO2 approximately from 20 to 25 mmHg; p< 0.001). This increase is largely attributable to growing umbilical venous PaO2, regardless of delivery modalities. In neonates born by vaginal delivery, the increased oxygen availability is associated with a modest increase in oxygen extraction, while in neonates born by cesarean section, it is associated with reduced lactate production. Independently from the type of delivery, carbon dioxide production moderately increased. These findings suggest a progressive shift from a prevalent anaerobic metabolism (Warburg effect) towards a growing aerobic metabolism. Conclusions. This study confirms that fetuses grow in a hypoxic environment that becomes progressively less hypoxic in the last weeks of gestation. The increased oxygen availability seems to favor aerobic metabolic shift during the last weeks of intrauterine life; we hypothesize that this environmental change may have implications for fetal maturation during intrauterine life.